High level of variation among Sri Lankan weedy rice populations, as estimated by morphological characterization. Issue 1 (March 2014) - Ratnasekera, Disna; Perera, Udugahapattuwage I.P.; He, Zhuoxian; Senanayake, Senanayakage G.J.N.; Wijesekara, Gamage A.W.; Yang, Xiao; Lu, Baorong
<x xml:space="preserve">Abstract</x> Weedy rice (Oryza sativa f. spontanea) is a notorious weed that infests paddy fields worldwide. Understanding the morphological variation pattern of this weed in a given rice‐planting region will facilitate its effective management and use. Here, 29 populations, covering nearly all the rice‐cultivation regions in Sri Lanka, were characterized in a common‐garden cultivation experiment that was based on 13 morphological traits. The variation level of the weedy rice populations was considerably high, as estimated by the Simpson and Shannon–Weaver indices. An ANOVA revealed a higher level of among‐population variation than within‐population variation. Seed shattering was the most variable trait and the seed length and width were the least variable traits, as indicated by their coefficient of variation. The results of the principal component analysis, in which the first two principal components represented 57.5% of the total variation, indicated the important role of such traits as plant height, seed weight and number of tillers and panicles in the divergence of the weedy rice populations. However, the variation was not associated with their geographical locality. Knowledge of such a morphological variation pattern provides opportunities to design strategic management methods for weedy rice control in Sri Lanka, in addition to the proper use of it as a genetic resource for rice improvement.